Pengaruh Model Pembelajaran Tipe Bamboo Dancing Terhadap Hasil Belajar Peserta Didik - Sahlan, Mohammad; Handayani, Suci; Hilmiyatun, Hilmiyatun; Listantia, Nora; Solihah, Fatimatus (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to determine the effect of Bamboo Dancing type learning on student learning outcomes at Mertak Tombok Public Elementary School. This research is experimental research. The technique used is pre and post test with a total of 20 multiple choice questions. The pre-test is carried out before the learning process ends, carried out to determine students' main skills in the material to be studied, which consists of 20 multiple choice questions. The results of this research are that the application of the bamboo dance cooperative learning model can improve student learning outcomes with a post-test score of 72.28 in the experimental class and 64.25 in the control class. And the results of the independent t test were 0.01 in the experimental class and 0.02 in the control class.